Golf by the numbers - Minton, Roland B., 1956- (Johns Hopkins University Press, 2012)
How do the world's greatest golfers improve their game? Practice, sure, but Roland Minton says mathematics and statistics are also key to their success. Golf by the Numbers analyzes the mathematical strategies behind the sport, giving fans a behind-the-scenes look at how numbers drive the game of golf. Computers, GPS trackers, swing simulators and high-speed cameras have introduced new and exciting ways of seeing and understanding the complicated and endlessly fascinating game of golf. Players like Phil Mickelson are so good because they review the results of every swing they take. Minton's comprehensive analysis of statistics from the PGA Tour's ShotLink system walks readers through the mountains of data that inform and refine the game of golf. The result is an insider's perspective of how the world's greatest golfers are adding up. Minton discusses randomness in golf (especially how much luck is involved in putting) and aggressive and cautious strategies both on and off the greens, and he explains, by the numbers, just how Tiger Woods was so dominant from 2004 to 2009. Here is a book that tells some truly engaging stories of modern golf, featuring famous players and memorable tournaments, all through the lens of elementary probability theory. Minton's informal style and clear and direct explanations make even the most detailed discussions accessible to all curious-minded golfers. His mathematical morsels are not only enjoyable to read, they may even help you play better.